(3XGgQI GdYhdeI hehba GdESdGe efgGs - (3djdi SdjeGf Ydj(B, (3HcQs ((3GdGScfOQjI(B:s (3OGQ GdacQ GdLGeYj,s, 2006)
(3jVe JYQja GdYhdeI hGdaQb HjfgG hHjf GdYGdejI, fTCI GdYhdeI hGdCOhGQ GdJj eQJ HgG, eLGdGJ GdYhdeI, TYGQGJ GdYhdeI hehba GdGSdGe efgGs
(3HjHdjhZQGajG(B: (3U(B.181s
Keywords: (3GdGSdGes; (3GdYhdeIs